Controlling factors of reservoir quality in low-permeability reservoir within a sequence stratigraphic framework: a case study of the lower Jurassic sandstones in the Northern margin of the Qaidam Basin, China. Issue 4 (19th May 2019) - Ren, C.-Q.; Gao, X.-Z.; Zhang, Y.-S.; Wang, B.; Hou, Z.-S.; Li, J.-M.; He, F.-G.
Abstract: The Qaidam Basin, one of China's most prolific petroliferous basins, is located in the northeastern corner of the Qinghai-Tibet Plateau. Using analytical data from cores, thin-sections and seismic data, and combined with the previous sequence stratigraphy research results, research on the reservoir characteristics was undertaken. The main controlling factors of reservoir quality in the sequence stratigraphy framework in the Lenghu area are discussed. The Lower Jurassic includes lowstand system tract (LST) and transitional systems tract (TST); the highstand systems tract are missing owing to tectonic uplift. The Lower Jurassic sandstones are composed of moderately to poorly sorted, subrounded sandstone representing several representative environments, including fan-delta and lacustrine facies. The main types of the Lower Jurassic sandstones are mostly feldspathic litharenite and lithic sandstone. The pore types of the Lower Jurassic sandstones are mainly secondary dissolution pores with few fracture types. The Lower Jurassic sandstones have experienced strong compaction that resulted in the loss of primary porosity. Carbonate cementation of the LST sandstones is greater than in the TST sandstones. Dissolution, which has an important role in reservoir development, is mainly caused by acidic fluids from the matured source rocks in the LST and meteoric water ingression from the top sequence boundary in the TST. Distributary channel sandstones adjacent to coal and mudstones are favourable reservoirs with turbidite sandstones adjacent to the sequence boundary less favourable reservoirs.